2009
DOI: 10.1111/j.1476-5381.2008.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+‐calmodulin can activate and inactivate cardiac ryanodine receptors

Abstract: ) on the gating of native sheep RyR2, reconstituted into bilayers. Suramin displaces CaM from RyR2 and we have used a gel-shift assay to provide evidence of the mechanism underlying this effect. Finally, using suramin to displace endogenous CaM from RyR2 in permeabilized cardiac cells, we have investigated the effects of 50 nmol·L -1 CaM on sarcoplasmic reticulum (SR) Ca 2+-release. Key results: Ca 2+CaM activated or inhibited single RyR2, but activation was much more likely at low (50-100 nmol·L -1 ) concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
(151 reference statements)
2
12
0
Order By: Relevance
“…Indeed, this was also observed by Sigalas et al. () who showed that the SR Ca 2+ ‐ATPase in permeablized cardiac cells was not affected by Suramin treatment for a similar time.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Indeed, this was also observed by Sigalas et al. () who showed that the SR Ca 2+ ‐ATPase in permeablized cardiac cells was not affected by Suramin treatment for a similar time.…”
Section: Discussionsupporting
confidence: 82%
“…Taken together, the results indicate that the Suramin effect on the SR Ca 2+ -ATPase is fully reversible. Indeed, this was also observed by Sigalas et al (2009) who showed that the SR Ca 2+ -ATPase in permeablized cardiac cells was not affected by Suramin treatment for a similar time.…”
Section: Effect Of Suramin On Sr Ca 2+ -Handlingsupporting
confidence: 76%
See 2 more Smart Citations
“…In addition, CaM can inhibit the opening of the calcium release channel by binding with RyR2, and can inhibit the binding of ryanodine and RyR2 to achieve the open and close balance of calcium release channels. [13][14][15] This study indicated that the mRNA and protein expression levels of CaM were significantly decreased by hypaconitine. Although the CaM mRNA expression level of the liquiritin plus high-dose hypaconitine group had no significant difference as compared with the control, the CaM protein expression level was significantly lower than that of the control and the high-dose hypaconitine group.…”
Section: Discussionmentioning
confidence: 77%